INSTALLATION OF ELECTRONIC DETECTION DEVICES ON PERSONS OF SEXUAL VIOLANCE AGAINST CHILDRENS (PROBLEMATICS AND SOLUTIONS) - Alifa, Virgie Kesfian; Harefa, Beniharmoni (LPPM STIH Putri Maharaja, 2023)
Electronic detection devices are an additional penalty stipulated in Government Regulation Number 70 of 2020. However, since being enacted until now there has been no judge's decision deciding the additional penalty for installing this electronic detection device because there are many instruments in the regulation itself. This study aims to find out the problems and solutions related to the application of the installation of electronic detection devices to perpetrators of sexual violence against children. This research leads to normative juridical law research, with data collection carried out by means of document studies. The results of the research found that there were several problems in the rules regarding the application of installing electronic detection devices so that later by doing comparisons a solution was found for some of the problems stipulated in PP 70/2020.